IB-MECA, an adenosine A(3) receptor agonist, does not influence survival of lethally γ-irradiated mice - Hofer, M; Pospíšil, M; Dušek, L; Hoferová, Z; Komůrková, D (Physiological research, 2012)
In our previous studies, IB-MECA, an adenosine A(3) receptor agonist, was found to stimulate proliferation of hematopoietic progenitor and precursor cells in mice. This property of IB-MECA was considered to be responsible for its ability to support regeneration of suppressed hematopoiesis after irradiation with sublethal doses of γ-rays when the drug was given in a post-irradiation treatment regimen. This study was aimed at assessing the ability of IB-MECA to influence a 30-day survival of lethally irradiated mice. In a series of experiments, IB-MECA was administered following various lethal radiation doses in various numbers of drug doses and various administration routes. Though in some of these experiments a moderate increase in 30-day survival was observed in IB-MECA-treated mice, the differences in comparison with the controls were not significantly different. It can be inferred from these results and those of previous studies assessing the effects of IB-MECA after sublethal radiation doses that IB-MECA can probably influence only a substantially preserved hematopoiesis like that remaining after sublethal irradiation. Future studies should be aimed at evaluation of the abilities of IB-MECA to influence post-irradiation survival when administered as a part of combined treatment regimens.
Keywords: agonisté adenosinového receptoru A3; záření gama; Animals; Mice, Inbred Strains; Adenosine; Gamma Rays; receptor adenosinový A3; inbrední kmeny myší; Radiation Injuries, Experimental; adenosin; Mice; myši; Hematopoiesis; Male; experimentální radiační poranění; Adenosine A3 Receptor Agonists; Receptor, Adenosine A3; hematopoéza; zvířata; mužské pohlaví